Brominated bitter compounds from the skin tubercle gland of the stonefish Synanceia verrucosa - Kawabe, Ryoya; Hoshi, Sota; Hifumi, Toru; Yamamoto, Akihiko; Uchida, Hajime; Satake, Masayuki; Nagai, Hiroshi (Bioscience, biotechnology, and biochemistry, 2025)
The skin tubercle gland of the stonefish Synanceia verrucosa secretes “ichthyocrinotoxin.” Ichthyocrinotoxins have been suggested to act as antifeedants against predators and as anthelmintics against parasites. Three novel compounds, synanceins A (1), B (2), and C (3), were isolated from S. verrucosa skin tubercle gland secretions as the major compounds. Their absolute structures were determined unambiguously by synthesizing molecular fragments and applying a modified Mosher's method. Compounds 1-3 are the first examples of brominated natural products from vertebrates. These compounds did not show any toxic activity against the L1210 cell lines and a marine diatom at a concentration of 100 μm. However, three researchers, who were the subjects, perceived a strong bitter taste at 10 μg of compounds 1-3. Synanceins A (1), B (2), and C (3), the major compounds in the ichthyocrinotoxin fraction of S. verrucosa, may play important roles as anthelmintics and antifeedants.